PROFIL PENGGUNAAN OBAT TRADISIONAL PADA MASYARAKAT DESA PEGANDON KENDAL - Suwarni, Sri; Septiyana, Ria; Fajaryanti, Nita; Indrasari, Ferika (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2023)
This study discusses the profile of the use of traditional medicine in Pegandon Village, where this study aims to obtain an overview of traditional herbal medicine producers in the Pegandon village area and an overview of the use of traditional medicine in traditional herbal medicine businesses in the Pegandon village area. This research was conducted using a descriptive method with a questionnaire as a data collector. The respondents in this study were the Pegandon village community. The results of the study showed that the highest use of traditional medicine in Pegandon village was women (100%), aged 31-40 years (40%), housewife (92%), last high school education (47.7%). Most of the types of illness were diarrhea (30%) and menstrual pain (30%) with a duration of illness that was mostly experienced less than one week (96%), most of the actions taken when sick by respondents were to see a doctor, health center or hospital (68%), most of the purpose of using traditional medicine is to cure a sudden/mild illness (34%) by buying traditional medicine at a traditional herbal medicine seller (42%), the dosage form most respondents use is in the form of herbal medicine (46%) with the average duration of use is 1 day (46%), the most sources of information are obtained from family (30%) on the grounds that they are made from natural ingredients (90%), the amount of use is mostly one tablespoon (40%) , the traditional medicine that is used mostly does not cause side effects (92%), when side effects appear some respondents still continue traditional medicine (2%), but there are those who go to the doctor or switch to modern medicine (40%), and there are who stopped using traditional medicine (58%). Keywords: traditional medicine, pegandon village